Analisis Pengelolaan Risiko pada Layanan Digital Banking Bank BNI - Ida Ayu Nuh Kartini; Mohammad Luqman Farandila; Bimantara Putra Ernanto; Rafi Putra Indriarto; Muhammad Thufail Musta’in (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The use of digital technology in the banking sector has changed the way people conduct transactions. Digital banking has now become the primary choice for banks to provide practical and fast services. Bank Negara Indonesia (BNI) is actively developing digital services to improve service quality. However, digital services also pose risks that can affect the security and stability of the banking system. This study focuses on identifying the risks in the use of digital banking and the risk management practices implemented by BNI. The research uses a descriptive qualitative approach with techniques of interviews, observation, and document review. The findings show that BNI's risk management is effective, although customer awareness of digital security needs to be improved.